Genetic parameters for tonic immobility, body weight, and morphological traits of the red-winged tinamou (Rhynchotus rufescens) - Santos, Dimas de Oliveira; Araujo Neto, Francisco Ribeiro de; Abreu Santos, Daniel Jordan de [UNESP]; Santos, Fabiana Ramos dos; Aspilcueta-Borquis, Rusbel Raul; Queiroz, Sandra Aidar de [UNESP]; Tonhati, Humberto [UNESP] (Springer, 2020)
This study was carried out to estimate genetic parameters for morphology, body weight, and tonic immobility traits in the red-winged tinamou (Rhynchotus rufescens). Information on 690 birds was used and genetic parameters were estimated using Bayesian methods under a multi-trait animal model. The following traits were considered in this study: tarsal length (TL), bill length (BL), wing length (WL), head width (HW), bill width (BW), mature weight (MW), weight at 90 days (W90), and tonic immobility (TI). The heritability showed estimates between 0.15 for wing length and 0.56 for bill length. Positive and negative genetic correlations were estimated, ranging from - 0.33 to 0.81. All the morphological, production, and behavioral traits studied will have moderate to high response to selection. The body weight at 90 days is a better alternative for use in breeding programs and its selection would not lead to an increase in the time of tonic immobility. Both the selection for weight gain and for reduction of tonic immobility time would lead to an increase in the size of the legs of the red-winged tinamou, which could be advantageous for thermal control of these birds in tropical systems.
Keywords: Poultry; Bayesian inference; Breeding program; Domestication